Karakterisasi Nilai Nutrisi Tulang Ayam Ras Broiler Melalui Analisis Proksimat - Kristantri, Rika Sebtiana; Tris Harni Pebriani; Wulan Kartika Sari (Universitas Qamarul Huda Badaruddin, 2024)
Chicken is a source of animal protein that is widely consumed by people because of its diverse nutritional content. Protein plays an important role as a source of macronutrients in the formation of biomolecules that make up more than part of cells, namely as the main component of enzymes as biocatalysts in various metabolic processes in the body. The increasing consumption of chicken is also accompanied by chicken bone waste, which has not been widely used. The bone contains 60% inorganic components, 30% organic components, and 10% air. The aim of this research is to identify the chemical properties of bones through several stages of testing that will be carried out. The testing stage, namely chicken bone preparation, is carried out by cleaning the chicken bone samples from dirt and meat remains that are still attached to the bones, then washing using running water until clean. The chicken bones were then dried in an oven at 70°C for ± 2 days, then ground using a grinder until smooth and sifted using a 60/100 mesh sieve. Sifting aims to uniformize the size of the dried chicken bone powder and make the next process easier. Dried chicken bone powder was tested for content in the form of determining water, ash, crude protein, crude fat, and crude fiber content. The results of the proximate value test were that dry chicken bones contained 9.10% water, 29.11% ash, 46.81% crude protein, 11.14% crude fat, and 0.88% crude fiber.